VD_FINDINFO Jug / 2025 / 10 vom 23. Mai 2024 - VD Tribunal cantonal (2024)
CONCOURS D'INFRACTIONS, PHYTOTHÉRAPIE, RESPONSABILITÉ RESTREINTEDROIT PÉNAL | 19 al. 2 CP, 49 al. 1 CP, 56 al. 3 CP, 60 CP, 63 CP